Prediction of vertical deflections from high-degree spherical harmonic synthesis and residual terrain model data - Hirt, Christian (Springer - Verlag, 2009)
This study demonstrates that in mountainous areas the use of residual terrain model (RTM) data significantly improves the accuracy of vertical deflections obtained from high-degree spherical harmonicsynthesis. The new Earth gravitational model EGM2008 is used to compute vertical deflections up to a spherical harmonic degree of 2160. RTM data can be constructed as difference between high-resolution SRTM (Shuttle Radar Topography Mission) elevation data and the terrain model DTM2006.0 (a spherical harmonic terrain model that complements EGM2008) providing the long-wavelength reference surface. Because these RTM elevationsimply most of the gravity field signal beyond spherical harmonic degree of 2160, they can be used to augment EGM2008 vertical deflection predictions in the very high spherical harmonic degrees.In two mountainous test areas - the German and the Swiss Alps - the combined use of EGM2008 and RTM data was successfully tested at 223 stations with high-precision astrogeodetic vertical deflections from recent zenith camera observations (accuracy of about 0.1 arc seconds) available. The comparison of EGM2008 vertical deflections with the ground-truth astrogeodetic observations shows RMS values (from differences) of 3.5 arc seconds for $ξ$ and 3.2 arc seconds for $η$, respectively. Using a combination of EGM2008 and RTM data for the prediction of vertical deflections considerably reduces the RMS values to the level of 0.8 arc seconds for both vertical deflection components, which is a significant improvement of about 75 percent. Density anomalies of the real topography with respect to the residual model topography are one factorlimiting the accuracy of the approach.The proposed technique for vertical deflection predictions is based on three publicly available data sets: (1) EGM2008, (2) DTM2006.0 and (3) SRTM elevation data. This allows replication of the approach for improving the accuracy of EGM2008 vertical deflection predictionsin regions with a rough topography or for improved validation of EGM2008 and future high-degree spherical harmonic models by means ofindependent ground truth data.